Victim or Villain? Racial/Ethnic Differences in News Portrayals of Individuals with Mental Illness Killed by Police. Issue 2 (2nd April 2020) - Frankham, Emma
ABSTRACT: As a social problem, little is known about how individuals are portrayed in the news when race/ethnicity and mental illness intersect. This is important because of the agenda-setting ability of the news. This article examines how individuals with mental illness who were killed by police during 2015 and 2016 were portrayed in the news. An examination of 301 news reports indicates that mental illness is particularly emphasized in news reports about whites with mental illness, and less so in news reports about African Americans or Hispanics with mental illness. Findings have implications for public attitudes about mental illness across race/ethnicity.